(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article analysis the traditional grammar and modern linguistics, and mainly reveals their similarities and differences. It is clear that linguistics is a science of linguistic study, which starts from descriptive grammar, structure grammar, functional grammar, transformational-generative grammar and many other grammars. It points out that though they are quite different, traditional grammar is the base from which modern linguistics is derived